Production of Instant Masam Jing Seasoning With Variation of Temperature and Drying Time - Reja Maqbul Armento (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Abstract. Masam Jing is a traditional cuisine typical of the Gayo highlands, Takengon City, Central Aceh Regency. This study aims to make instant Jing Masam seasoning so that it can facilitate use and study the effect of temperature and drying time on the quality of instant Jing Sour seasoning. This study used a randomized block design (RBD) with 2 factors. The first factor is the drying temperature (T), with 3 levels which was T1 = 45 ° C, T2 = 50 ° C and T3 = 55 ° C. The second factor is the drying time (L), with 3 levels which was L1 = 8 hours, L2 = 9 hours, L3 = 10 hours. The treatment combination was carried out 3 x 3 = 9 with 3 replications. So that we get 27 experimental units. The results of this study indicated that the drying temperature treatment (T) had a significant effect (p≤0.05) on the moisture content, ash content, and the resulting hedonic taste test. The drying time treatment (L) had a significant effect (p≤0.05) on the moisture content, ash content, and the resulting hedonic taste test. While the interaction treatment of the two was not significant (p0.05) on moisture content, ash content, and organoleptic tests. The best treatment was obtained at a drying temperature of 50 ℃ and a drying time of 10 hours (T2L3).